Simultaneous Application of High-Intensity Focused Electromagnetic and Synchronized Radiofrequency for Fat Disruption: Histological and Electron Microscopy Porcine Model Study. Issue 8 (August 2021) - Weiss, Robert A.; Bernardy, Jan; Tichy, Frantisek
Abstract : BACKGROUND: Radiofrequency (RF) and high-intensity focused electromagnetic (HIFEM) technologies are used for noninvasive body shaping as standalone modalities. OBJECTIVE: To examine the effects of novel synchronized RF and HIFEM on subcutaneous adipose tissue in a porcine animal model. MATERIALS AND METHODS: Seven large white pigs aged 6 months received 3 abdominal treatments of simultaneous application of synchronized RF and HIFEM (30 minutes, once per week). Punch biopsies of treated and control subcutaneous tissue were collected at the baseline, 4 days, 2 weeks, 1 month, and 2 months. Specimens were examined by light and scanning electron microscopy. Adipocyte volume was analyzed. Fat tissue temperature was measured in situ (fiber optic probes) and superficially (thermal imager). RESULTS: Fat layer was heated to temperatures of 42 to 45°C. Signs of fat apoptosis (shape alternations and pyknotic nuclei) appeared at day 4 and peaked between 2 weeks and 1 month. Adipocyte volume decreased significantly ( p < .001) by 31.1% at 2 weeks, 1 month (−23.6%), and 2 months (−22.0%). Control samples showed healthy adipocytes. Scanning electron microscopy micrographs corroborated histology findings, showing flattened, volume-depleted and disrupted adipocytes. CONCLUSION: Synchronized RF with HIFEM procedure resulted in a significant and sustained fat reduction with no adverse events.